Research on Emergency Brake Deceleration Rate of Metro Vehicles under Low-adhesion Condition - DUAN Jichao; GAO Xiaobo; WANG Weibo (机车电传动)
For ensuring the operation safety, emergency brake deceleration rate of metro vehicles under low-adhesion condition was studied. Firstly, the requirements about operation under the worst condition, regulated by related standards, were presented. Secondly, the principle of braking and the influence of adhesion was described. Thirdly, the research results on the adhesion at home and abroad were introduced. At last, the variation of emergency brake deceleration rate under low-adhesion condition was studied through theoretical calculation and line test. The test results are helpful for the operators to develop the safety measures when the vehicles are operated under low-adhesion condition.